HEPATOPROTECTIVE ACTIVITY OF Trichosanthes cucurmena L. - Palanisamy, Vaijayanthimala; Shanmugam, Sureshkumar; Balakrishnan, Sangameswaran (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: This study investigated the hepatoprotective activity of ethanolic extract of Trichosanthes cucumerina L. (EETC), in paracetamol induced hepatotoxic studies carried out in male albino rats and included to produce toxicity of the formulation. Methods: Albino rats (175 g) were taken and divided into four groups liver necrosis was induced by intraperitoneal injection of paracetamol (3 mg/ kg b.w, p.o). The hepatoprotective activity of EETC was evaluated by measuring levels of serum marker enzymes like serum glutamate oxaloacetate transaminase (SGOT), serum glutamate pyruvate transaminase (SGPT) and alkaline phosphatase (ALP). The serum levels of total proteins and bilirubin were also estimated. The histological studies were carried out to support the above parameters. Here Silymarin was used as standard drug. Result: Administration of EETC (150 mg/kg, p.o.) markedly prevented paracetamol-induced elevation of levels of SGPT, SGOT, ALP, and bilirubin. The decreased level of total proteins due to hepatic damage induced by paracetamol was found to be increased in EETC treated group. Conclusion: The results are comparable to the of silymarin. A histopathological study of liver exhibited almost normal architecture when compared with paracetamol treated group. Hence the hepatoprotective activity of EECT was proved. Keywords: Trichosanthes cucumerina L., Serum glutamate oxaloacetate transaminase, Serum glutamate pyruvate transaminase, Sylimarin and Paracetamol.